2004
DOI: 10.1029/2003jd004058
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving profiles of atmospheric CO2 in clear sky and in the presence of thin cloud using spectroscopy from the near and thermal infrared: A preliminary case study

Abstract: [1] The benefits and limitations of retrieving a typical source profile of CO 2 in the lower atmosphere employing high-resolution measurements from the 1.6 mm region in the near infrared (NIR) and moderate-resolution measurements from the thermal infrared (IR) are explored for clear-sky scenarios as well as scenarios containing thin cloud. With respect to CO 2 column-average values, the results of this study show that all errors in CO 2 column-average values were 1 ppmv or less for the cases considered. Retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…These results are close to those from previous studies (Christi and Stephens, 2004;Connor et al, 2008;Saitoh et al, 2009;Yoshida et al, 2011), but it is important to note that the absolute values of averaging kernel and error profile cannot be directly compared, since they depend on several parameters: (1) a priori values x a and x b , (2) the variability of the error covariance matrix S a , S f and S m , as well as (3) the vertical grid. The latter can be circumvented if the tropospheric column error (S XCO 2 ) is derived from the vertical profile error as in Yoshida et al (2011):…”
Section: Information Content Analysis Applied To Greenhouse Gas Profisupporting
confidence: 73%
See 2 more Smart Citations
“…These results are close to those from previous studies (Christi and Stephens, 2004;Connor et al, 2008;Saitoh et al, 2009;Yoshida et al, 2011), but it is important to note that the absolute values of averaging kernel and error profile cannot be directly compared, since they depend on several parameters: (1) a priori values x a and x b , (2) the variability of the error covariance matrix S a , S f and S m , as well as (3) the vertical grid. The latter can be circumvented if the tropospheric column error (S XCO 2 ) is derived from the vertical profile error as in Yoshida et al (2011):…”
Section: Information Content Analysis Applied To Greenhouse Gas Profisupporting
confidence: 73%
“…The CO 2 profile a priori error (red line of Fig. 2) is estimated from Schmidt and Khedim (1991) and is very similar to the one used by Christi and Stephens (2004). The CH 4 a priori error is fixed to P error = 5 %, which corresponds to an under-constrained version of the error covariance matrix used by Razavi et al (2009) andFrankenberg et al (2012).…”
Section: A Priori Error Covariance Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Unaccounted variability of aerosols and clouds (including cirrus) in the retrieval is an important error source for CO 2 measurements from space (Tolton and Plouffe, 2001;O'Brien and Rayner, 2002;Kuang et al, 2002;Dufour and Bréon, 2003;Buchwitz and Burrows, 2004;Buchwitz et al, 2005a;Christi and Stephens, 2004;Mao and Kawa, 2004;Houweling et al, 2005;van Diedenhoven et al, 2005;Barkley et al, 2006a;Aben et al, 2006;Bril et al, 2007) as aerosols are highly variable and their optical properties (e.g., vertical profiles of phase function, extinction and scattering coefficients) are not known for each scene observed from satellite. This results in aerosol and cloud related errors which are difficult to quantify.…”
Section: Aerosol Filteringmentioning
confidence: 99%
“…This approach has been used to estimate lower tropospheric ozone (Worden et al, 2007;Fu et al, 2012) and carbon monoxide (CO) . However, we do not use the direct profiling approach discussed in Christi and Stephens (2004), because we found that spectroscopic errors and sampling error due to poor co-location of the NIR and TIR data currently result in unphysical retrieved CO 2 profiles. Instead we simply subtract free tropospheric column estimates from total column estimates in order to quantify lower tropospheric CO 2 column amounts.…”
Section: Introductionmentioning
confidence: 99%